Human body - Bingham, Caroline, 1962-; Carter, Daniel (New York : DK Pub., 2003)
A brief introduction to the human body, including some facts about sleep.
Subtitle on cover: Open your eyes to a world of discovery.
Includes index.
Keywords: Human body -- Juvenile literature; Body, Human; Sleep